Analysis of the UMMI Method with the Independent Curriculum in Class X of MA An-Najah Jakarta - Yusril Ilham Suryadi; Muhammad Arifin Rahmanto (UMSU, 2026)
This study aims to analyze the application of the UMMI method in the implementation of the Merdeka Curriculum in 10th-grade Qur'an instruction at MA An-Najah, Jakarta. The background of this study is based on the importance of applying a Qur'an teaching method that does not only focus on academic achievement but is also capable of creating a learning environment that is enjoyable, engaging, and full of compassion, in line with the characteristics of the Merdeka Curriculum. This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that the UMMI method is effective in enhancing students' Qur'an reading skills and supporting the integration of religious values into daily life. This success is evident through the application of learning strategies such as imitating and repeating recitations, building emotional closeness between teachers and students, and creating a conducive learning atmosphere.